The generation of identity in late medieval hagiography : speaking the saint - Ashton, Gail, 1957- (London ; New York : Routledge, 2000)
In this interdisciplinary and boundary breaking study, Gail Ashton examines the depiction of female saints in a wide range of medieval texts.
Book Cover; Title; Contents; Acknowledgements; Abbreviations; Introduction; Narration and narratorial control: the masculine voice; A concept of space and a notion of identity; Articulating an identity: speech, silence, and self-disclosure; Written on the body; Conclusion: song of the saint; Bibliography; Index.
Includes bibliographical references (pages 162-171) and index.
Print version record.
Keywords: Christian women saints -- Biography -- History and criticism; Christian saints -- Biography -- History and criticism; Literature, Medieval -- History and criticism; Christian hagiography; RELIGION -- Christian Theology -- Angelology & Demonology; Christian hagiography; Christian saints -- Biography; Christian women saints -- Biography; Literature, Medieval; Hagiografie; Sekseverschillen; Vrouwen; Heiligen; Electronic books; Criticism, interpretation, etc